Influence of the Expression of Inflammatory Markers on Kidney after Fetal Programming in an Experimental Model of Renal Failure - Carlos Donizete Pereira Júnior; Camila Souza de Oliveira Guimarães; Aline Cristina Souza da Silva; Aldo Rogelis Aquiles Rodrigues; Maria Aparecida da Glória; Vicente de Paula Antunes Teixeira; Niels Olsen Saraiva Câmara; Lenaldo Branco Rocha; Marlene Antônia dos Reis; Juliana Reis Machado; Laura Penna Rocha; Fernanda Rodrigues Helmo; et al. (Journal of Immunology Research)
Objective. To evaluate the expression of inflammatory markers in experimental renal failure after fetal programming. Methods. The offspring aged two and five months were divided into four groups: CC (control dams, control offspring); DC (diabetic dams, control offspring); CFA (control dams, folic acid offspring, 250 mg/Kg); and DFA (diabetic dams, folic acid offspring). Gene expression of inflammatory markers MCP-1, IL-1, NOS3, TGF-β, TNF-α, and VEGF was evaluated by RT-PCR. Results. MCP-1 was increased in the CFA and DFA groups at two and five months of age, as well as in DC5 when compared to CC5. There was a higher expression of IL-1 in the CFA2, DFA2, and DC2 groups. There was a decrease in NOS3 and an increase in TNF-α in DFA5 in relation to CFA5. The gene expression of TGF-β increased in cases that had received folic acid at two and five months, and VEGF decreased in the CFA5 and DFA5 groups. DC5 showed increased VEGF expression in comparison with CC5. Conclusions. Gestational diabetes mellitus and folic acid both change the expression of inflammatory markers, thus demonstrating that the exposure to harmful agents in adulthood has a more severe impact in cases which underwent fetal reprogramming.